POLITICAL INSTITUTIONAL CONDITIONS AND COLLECTIVE VIOLENCE - Jastramskis, Mažvydas (Politologija, 2015)
Collective violence has been a concern for the social sciences since the Antiquity. However, precisely in the last decades academic interest in this phenomenon is increasing. It could be related both to the violent character of the 20th century (in terms of absolute and relative numbers of casualties) and changing nature of violent conflict: rising death toll of civilians, spread of inner-state ethnic and civil violence, decline of traditional warfare, etc. This article is focused on the aspect of political institutional conditions (regime properties): how they are related to the collective violence. Relying on works of Charles Tilly, two most important properties of regimes (political institutional conditions) that could affect the occurrence and intensity of collective violence are discerned: regime (governmental) capacity and democracy level. Three hypotheses are discerned for the empirical testing. First hypothesis presupposes inverse relation between the democracy level and degree of collective violence (except inter-state warfare). Second hypothesis similarly enunciates the inverse relation between the regime capacity and degree of collective violence (initiated by the non-governmental subjects). According to the third hypothesis, highest levels of collective violence should be expected in the low capacity-undemocratic regimes, moderate levels – in low capacity-democratic and high capacity-undemocratic, lowest levels – in high capacity-democratic regimes. Testing of hypotheses is based on quantitative-graphical analysis, using the data on democracy and political collective violence provided by the Center for Systemic Peace. First hypothesis is falsified – in accordance with other similar works (f.e., Gupta, 2008), no relation between democracy level and degree/occurrence of collective violence is found. However, empirical analysis strongly supports the second hypothesis: there is a statistically significant relationship between the regime capacity (measured as polity fragmentation index) and degree of collective violence. The probability that regime will experience higher levels of collective violence (if it occurs) is raised greatly when the regime capacity is lower. As it is expected from these findings, third hypothesis is only partially supported: higher levels of collective violence are indeed observed in the low capacity-undemocratic regimes, but the most successful in terms of containment of collective violence are high-capacity undemocratic regimes (not high capacity-democratic, as formulated in the hypothesis).